Síntese de pigmentos inorgânicos por incorporação de componentes de pilhas alcalinas e pilhas zinco-carbono exauridas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Every industrial process generates waste that often may be toxic or dangerous to human health and the environment. In Brazil, about 1.2 billion units of batteries are produced annually, which are unfortunately still irregularly disposed of, contaminating the soil, water, air and presenting a risk to human health. Thus, the use of industrial waste appears as an important strategy to protect and promote the environment. One of the alternatives for the reuse of residues is the synthesis of pigments. In this context, the objective of the present work was to synthesize inorganic pigments, by solid state reaction, from the incorporation of components of alkaline batteries and exhausted zinc-carbon cells. The obtained pigments were characterized by X-ray diffractometry, scanning electron microscopy by field effect, laser particle size and diffuse reflectance spectroscopy in the ultraviolet-visible region. The chemical stability of the pigments was analyzed from solutions of 10 % (v/v) sulfuric acid and 10 % (w/v) sodium hydroxide. The thermal stability, in turn, was evaluated in two stages, the first one by thermogravimetry and the second by application in ceramics. The feasibility of applying the pigments in paints and polymers was also analyzed. Based on the analyzes, it was possible to observe that the pigments PAZC33 and PAZR33 presented the best results for application in paints, polymers and ceramics. Finally, it was concluded that the incorporation of the components of batteries, allowed, in general, the production of black and brown pigments with a structure of spinel type ZnMn2O4 and that they have commercial potential.
Keywords: pigmentos inorgânicos; espinélios; pilhas; reciclagem; cor; inorganic pigments; spinels; batteries; recycling; color; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA